Nilai Karakter Pada Lirik Lagu-Lagu Kids United (Universitas Negeri Semarang, 2020)
Learning French in class always pays attention to 2 aspects namely cognitive and moral. Moral aspects also have a role in the development of students, so that they have good morals and personalities such as learning to adapt in the school environment to foster a sense of tolerance in order to be able to control their own emotions while also having high knowledge. The purpose of this research is to describe the character value contained on the songs of Kids United and linguistics elements expressing the character value. This type of research is a descriptive research with a qualitative approach. Whereas the data collection methods used in this research are the listening method and the note technique. Then the results of data analysis in this research indicate that Kids United’s three songs contain 3 dominant character values ​​from eight national character values ​​according to IHF, such as (1) loving, caring and cooperate; (2) confident, creative, hard work and never give up; (3) responsibility, discipline and independent.